2008
DOI: 10.1371/journal.pone.0001886
|View full text |Cite|
|
Sign up to set email alerts
|

Paracrine Factors of Mesenchymal Stem Cells Recruit Macrophages and Endothelial Lineage Cells and Enhance Wound Healing

Abstract: Bone marrow derived mesenchymal stem cells (BM-MSCs) have been shown to enhance wound healing; however, the mechanisms involved are barely understood. In this study, we examined paracrine factors released by BM-MSCs and their effects on the cells participating in wound healing compared to those released by dermal fibroblasts. Analyses of BM-MSCs with Real-Time PCR and of BM-MSC-conditioned medium by antibody-based protein array and ELISA indicated that BM-MSCs secreted distinctively different cytokines and che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

50
1,207
7
11

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,396 publications
(1,304 citation statements)
references
References 40 publications
50
1,207
7
11
Order By: Relevance
“…Although macrophages are the major source of proinflammatory cytokines, neither the CD68 mRNA level nor immunostaining showed a reduction in macrophage infiltration after either MSC or GF treatment. The possibility that treatment with bone marrow-derived MSCs enhances wound healing by increasing the recruitment of macrophages to the wound site has been evoked [37]. Recruited macrophages induce granulation tissue and myofibroblast differentiation during the early stage of the repair and are crucial for the stabilization of vascular structures and the transition of granulation tissue to scar tissue during intermediate stages of repair [28].…”
Section: Figmentioning
confidence: 99%
See 2 more Smart Citations
“…Although macrophages are the major source of proinflammatory cytokines, neither the CD68 mRNA level nor immunostaining showed a reduction in macrophage infiltration after either MSC or GF treatment. The possibility that treatment with bone marrow-derived MSCs enhances wound healing by increasing the recruitment of macrophages to the wound site has been evoked [37]. Recruited macrophages induce granulation tissue and myofibroblast differentiation during the early stage of the repair and are crucial for the stabilization of vascular structures and the transition of granulation tissue to scar tissue during intermediate stages of repair [28].…”
Section: Figmentioning
confidence: 99%
“…Although M2 macrophages provide a source for VEGF [28], analysis of the MSC-conditioned medium indicated that MSC secretes many tissue repair mediators, including angiogenic proteins such as VEGFs and epithelial cell stimulatory proteins such as EGF and FGF7 [37]. Physiological levels of these growth factors are critical for ensuring wound healing [40].…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…Stem cells including mesenchymal stem cells (MSCs) and hematopoietic stem cells (HSCs) are recruited to a healing wound, where they support healing in a variety of ways 3, 4, 5, 6. The healing potential of stem cells has resulted in the development of stem cell therapies for the treatment of chronic wounds.…”
Section: Introductionmentioning
confidence: 99%
“…MSCs generate an array of cytokines and growth factors [15,56] that protect kidneys from injuries [15][16][17]57]. Therefore, we postulated that 14S,21R-diHDHA treatment enhanced the beneficial effects of MSCs by augmenting their secretion of renotrophic factors.…”
Section: S21r-dihdha Treatment Enhances Mmsc and Hmsc Secretion Ofmentioning
confidence: 99%